The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/20018525.2017.1327761
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms among Swedish soldiers after military service abroad: association with time spent in a desert environment

Abstract: Introduction: The aim of this paper was to study whether Swedish soldiers who have served abroad had a higher prevalence of respiratory symptoms than the general population and, if this was the case, also to study whether this was associated with time spent in a desert environment. Methods:The prevalence of respiratory symptoms among 1,080 veterans from Kosovo and Afghanistan was compared with that in almost 27,000 subjects from a general population sample, using propensity score matching and logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A retrospective questionnaire-based study of Swedish military personnel who served primarily in Afghanistan (2008–2009) and who were surveyed 36 months to 5 years later found an increased prevalence of wheeze, wheeze without a cold, nocturnal coughing, and chronic bronchitis among soldiers compared with a referent group of civilians ( 82 ). A statistically significant relationship was found between months spent in a desert environment and wheeze, wheeze with breathlessness, and wheeze without a cold.…”
Section: Epidemiologic and Observational Studies In Previously Deploymentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective questionnaire-based study of Swedish military personnel who served primarily in Afghanistan (2008–2009) and who were surveyed 36 months to 5 years later found an increased prevalence of wheeze, wheeze without a cold, nocturnal coughing, and chronic bronchitis among soldiers compared with a referent group of civilians ( 82 ). A statistically significant relationship was found between months spent in a desert environment and wheeze, wheeze with breathlessness, and wheeze without a cold.…”
Section: Epidemiologic and Observational Studies In Previously Deploymentioning
confidence: 99%
“…Studies conducted by DoD analyzing military encounter data suggest that more encounters occur for respiratory symptoms and for obstructive lung disease, predominantly asthma, after deployment ( 4 6 ). A study in Swedish troops deployed to Afghanistan also documented the persistence of symptoms several years after deployment ( 82 ). Case series describing the evaluation of symptomatic military personnel do not note any single etiology, emphasizing the importance of a comprehensive clinical assessment, but asthma has been a common finding (References 8 and 75 and S. D. Krefft, workshop presentation of unpublished data).…”
Section: Summary and Key Questionsmentioning
confidence: 99%
“…Studies conducted by DoD analyzing military encounter data suggest that more encounters occur for respiratory symptoms and for obstructive lung disease, predominantly asthma, after deployment (4-6). A study in Swedish troops deployed to Afghanistan also documented the persistence of symptoms several years after deployment (82). Case series describing the evaluation of symptomatic military personnel do not note any single etiology, emphasizing the importance of a comprehensive clinical assessment, but asthma has been a common finding (References 8 and 75 and S. D. Krefft, workshop presentation of unpublished data).…”
Section: Adverse Respiratory Health Effectsmentioning
confidence: 99%
“…Inhalation of particulate matters with a diameter below 10 and 2.5 μm (PM 10 and respectively PM 2.5) may lead to cytotoxic and proinflammatory effects in the airways, and associations of exposure to PM 10 and PM 2.5 have been reported for airway diseases like pneumonia, lung cancer, asthma, and chronic obstructive pulmonary disease (COPD) [1][2][3][4][5][6][7]. Several studies have reported respiratory symptoms and conditions among military personnel after service in countries with recurrent desert storms, suggesting that exposure to different small particles during desert storms could contribute to the development of respiratory disease [8][9][10][11][12][13][14]. A number of studies have also reported that increased respiratory hospitalisations in European countries such as Italy, Greece and Cyprus are associated with temporary dust spreading from desert storms originating in Sahara [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In populations permanently staying in areas with repeated desert storms, several studies have compared subjective symptoms and objectives measures such as peak expiratory flow and reported worsening during periods of heavy dust exposure, both in previously healthy people and in participants with asthma [22][23][24]. As for military personal with temporary exposure for desert storms, several studies have reported worsened symptoms and spirometry after deployment [8][9][10][11][12][13][14], and a significant difference towards non-exposed populations [13], but to our very best knowledge, studies of specific exposure to particulate matter combined with a comparison of objective measures of spirometry and fraction of nitric oxide (FeNO) before and after exposure to desert storms are still lacking.…”
Section: Introductionmentioning
confidence: 99%